"The joy to bless and to relieve mankind": child healthcare at Northampton General Infirmary 1744. Issue 12 (21st November 2005) - Williams, A N
Abstract : For more than a century before the opening of Great Ormond Street Hospital for Children (1852), children in England were treated and even admitted in voluntary hospitals in spite of rules prohibiting such care. The earliest English eighteenth century records, that contain the patient's age, are held in Northampton. Reviewing records from the Northampton General Infirmary (from 1903 the Northampton General Hospital) for the period 1744–45 gives a flavour of hospital child health care in an era before the formal recognition of paediatrics as a medical specialty and the construction of specialist provision. Indeed the first patient admitted to the Northampton General Infirmary on 29 March 1744 was Thomasin Grace, a 13 year old child. In Northampton, in its first year of operation, children as young as 2 years of age were seen in outpatients and from 8 years were admitted. Paediatric cases up to and including those 16 years of age made up 26% of the number of patients seen for that year. Within the first year of opening for children of 10 years of age and under, there were eight inpatient admissions and 18 children were treated in outpatients.